Softening Behavior of Black Sweet-Bamboo (Dendrocalamus asper Backer) at Various Initial Moisture Contents - MATAN, Nirundorn; KYOKONG, Buhnnum; PREECHATIWONG, Wanchart (Walailak Journal of Science and Technology (WJST), 2011)
Softening behavior of bamboo (Dendrocalamus asper Backer) at various initial moisture contents (0 %, 13 %, 37 % and 60 %) was investigated by means of dynamic mechanical thermal analysis (DMTA). The tests were performed in a bending mode over a temperature range of 0 - 300 °C. A heating rate of 3 °C/min with a constant oscillation strain of 0.1 % at a frequency of 1 Hz was employed. It was found that at low temperature the storage modulus of the bamboo decreased with increasing temperature. The glass transition temperature of bamboo with higher initial moisture content was lower than that of bamboo with lower initial moisture content. Moisture content changes at lower levels (<13 %MC) had a greater effect on the glass transition temperature than moisture content changes at higher levels (>13 %MC). Moreover, free water in the cell cavity appeared to have little effect on the glass transition temperature. The maximum and minimum glass transition temperatures of the bamboo were 194±10 °C and 85±10 °C and were obtained from oven dried bamboo and water saturated bamboo, respectively. Relaxation of lignin at various moisture conditions was proposed to be a major mechanism responsible for the softening of the bamboo cell wall. At very high temperatures beyond the temperature of maximum loss tangent, storage modulus increased with increasing temperature which could be a result of the presence of a more crystalline cellulose phase caused by the heating.